Examining the impact of justice perceptions on workplace bullying: a moderated mediational model of PCV and PDO. Issue 2 (18th July 2020) - Rai, Arpana; Agarwal, Upasna A.
Abstract : Purpose: The purpose of this paper is to examine the relationship between justice perceptions (distributive, procedural and interactional) and workplace bullying and to test the mediating role of psychological contract violation (PCV) in this relationship and the extent to which the mediation is moderated by power distance orientation (PDO). Design/methodology/approach: The study draws upon quantitative data collected via self-reported survey questionnaires from 422 full-time Indian managerial employees working across different service sector–based Indian organizations. Findings: The results revealed that justice perceptions (distributive, procedural and interactional) negatively correlated with workplace bullying. The hypothesized moderated mediation condition was supported as the results suggest that the PCV mediated the justice-bullying relationship and the PDO moderated this mediating pathway, i.e. indirect effects of justice (procedural and interactional) perceptions on workplace bullying via PCV were weaker for employees with a high PDO. Research limitations/implications: A cross-sectional design and the use of self-reported questionnaire data in the sample are few limitations of the study. Practical implications: This study contributes toward a better understanding of the relationships between justice, PCV and workplace bullying. It also highlights the role played by individual cultural dispositions in influencing their perceptions of workplace bullying. Given the perceptual and subjective elements of workplace bullying, understanding how justice and workplace bullying are related in not only important theoretically but also critical from a practical standpoint. Originality/value: To the best of authors' knowledge, this is the first study that links justice, PCV, workplace bullying and PDO in one study. This study is also important in terms of its context.